Determinants of health-related quality of life in patients with fracture of the axis vertebrae - Andzelina Wolan-Nieroda (Nature Portfolio, 2021)
Abstract The study is designed to evaluate quality of life and functional performance in patients with type II and III odontoid fracture treated with anterior odontoid screw fixation. We investigated the relationship between quality of life and: (1) the range of axial rotation of the cervical spine, (2) neck pain intensity, and (3) level of disability in these patients. The study involved 60 patients operated on for type II and III fractures with the use of direct osteosynthesis of the dens. Quality of life and functional performance were assessed using SF-36 Questionnaire and Neck Disability Index (NDI). The range of axial rotation was examined with the use of the Zebris ultrasound system while the intensity of pain with the use of the VAS Visual Analog Pain Scale. The subjects’ quality of life was poorer with respect to the mental dimension (32.3%) compared to the physical dimension (22.7%). Based on the NDI survey, the rate representing the patients’ functioning in daily life amounted to 13.7% which reflects mild limitations in functional abilities. It was shown that the range of axial rotation (both to the right and the left) was not related to the degree of disability of patients as measured by the NDI questionnaire. The model of regression was statistically significant for overall quality of life (F = 48.24 p < 0.001), as well as physical dimension (F = 45.1 p < 0.001). Quality of life indicators in SF-36 are decreased in patients operated for type II and III odontoid fracture and the mental dimension of the quality of life is significantly poorer than the physical one. More than half of the patients operated for type II and III odontoid fracture regained normal functioning, as assessed with the NDI questionnaire.